Youth in Fiji and Solomon Islands Livelihoods, Leadership and Civic Engagement - Craney, Aidan (Pacific Series, 2022)
Fiji, Solomon Islands and the wider Pacific region are experiencing a 'youth bulge'. As such, the livelihoods pathways of youth in these countries will be a key determinant of their social, political and economic futures. This book looks at the cultural expectations of Fijian and Solomon Islander youth, as well as the socio-political positioning of youth activists. It investigates how formal and informal structures - such as education, employment and civil society - affect the ability of youth to achieve their potential and actively engage in their societies. Through this investigation, a recurrent theme develops of the structural minimisation of youth in these countries: they are 'to be seen but not heard'. But Pacific youth are more than citizens in waiting; they are already important members of their communities, with varying degrees of engagement in critical civil society. More than simply leaders of tomorrow, they are partners for today. Youth in Fiji and Solomon Islands documents and details some of the ways that young people in Fiji and Solomon Islands are forging their way as leaders not just of youth, but of their communities. Whilst the majority of youth are engaging in society in acceptable, social ascribed ways, and the majority of adults resist youth participation as a technique to maintain the social status quo, a small but influential cohort of both youth and adults are creating spaces for today's young people to help to shape the developmental futures of the Great Ocean States of the Pacific.